A survey of motivational factors in the learning behaviour of students in Ho Polytechnic - Dargbe, Margaret Maxima (2011)
A Thesis submitted to the Department of Mechanical Engineering of the Kwarne Nkrumah University of Science & Technology, Kumasi in partial fulfillment of the requirements for the award of the degree of Master of Technical Education, 2002